Micro Waqf Bank: A Bibliometric-based VosViewer Analysis - Husain, Alfi Zikri; Cahyani, Utary Evy (International Journal of Waqf, 2024)
This study aims to see the development of research on the topic of "Micro Waqaf Bank" and the research plans carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Micro Waqaf Bank" which comes from the Demensions database with a total of 480 articles. Then, the data is processed and analyzed using the VosViwer application with the aim of knowing the bibliometric map of "Micro Waqaf Bank" research development in the world. The results of this study found that in bibliometric author mapping the authors who published the most research with the theme "Micro Waqaf Bank" were Del Baldo, Mara; Gundogdu, Ahmet Suayb; Devis; Scott T; Widiastuti, Tika; Sukmana, Raditya: and Syamlan, Yasser Taufik. Furthermore, based on bibliometric keyword mapping, there are 4 clusters that can become research lines with topics related to BWM and Finance, BWM and poverty, The Institution of BWM, and BWM in Indonesia. Furthermore, the most used words are Challenge, country, development, education, finance, financial inclusion, interest, Islamic banking, Islamic finance, SDGs, sustainability, community, fund, islam, philanthropy, poverty, principle, problem, society, waqf, zakat, BMT, business, cash waqf, data, financing, government, institution, management, model, role, waqf institution, and Indonesia. This research is expected to encourage future researchers to make more meaningful contributions and have a significant impact on the development and improvement of the Micro Waqf Bank model.